Mathematical modeling of biologically active filtration (BAF) for potable water production applications. (15th December 2019) - Sun, Yewei; Vaidya, Ramola; Khunjar, Wendell O.; Rosenfeldt, Erik J.; Selbes, Meric; Wilson, Christopher; Bott, Charles B.; Titcomb, Mark; Wang, Zhi-Wu
Abstract: In this study, a modeling framework was developed to simulate biologically active filtration (BAF) headloss buildup in response to organic removal and nitrification. This model considered not only the biofilm growth on the BAF media but also the particle deposition in the BAF bed. In addition, the model also took temperature effect into consideration. It was calibrated and validated with data collected from a pilot-scale study used for potable water reuse and a full-scale facility used for potable water treatment. The model prediction provided insights that biofilm growth rather than particle deposition primarily contributes to the headloss buildup. Therefore, biofilm control is essential for managing headloss buildup and reducing the backwash frequency. Model simulation indicated that the BAF performance in terms of pollutant removal per unit headloss is insensitive to the BAF bed depth but can be effectively improved by increasing the media size. The partial biofilm coverage of the media is confirmed in this study and was mathematically verified to be a prerequisite for the model fitness. Graphical abstract: Image 1 Highlights: We established a BAF model to simulate headloss due to biofilm and particle deposition. Model prediction is sensitive to the biofilm coverage of BAF media. Particle deposition contributed <1% to headloss in potable reuse treatment. Increasing the media size reduces headloss but slightly lowered COD and NH4 + removal. Increasing bed depth helps compensate COD and NH4 + removal decrease at larger media size.